2021
DOI: 10.3892/etm.2021.10497
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary approach in the diagnostic challenge of GIST

Abstract: Gastrointestinal stromal tumors (GISTs) are the most common malignant mesenchymal lesions of the gastrointestinal tract. They originate from the interstitial cells of Cajal and are characterized by overexpression of the tyrosine kinase receptor, protein product of c-KIT gene (KIT). In this retrospective study, conducted over a period of 10 years, we retrieved from our database, a total number of 57 patients, admitted and operated in the surgical department of 'Sf. Pantelimon' Emergency Clinical Hospital, Bucha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Pantelimon Emergency Clinical Hospital Bucharest (2011-2020) found that most tumour locations were stomach (49.12%) and sigmoid (3.5%) but no rectum. 12 Mesenchymal tumours of the prostate with spindle cell patterns required a comprehensive differential diagnosis. This case lacked specific clinical signs and symptoms, as well as laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pantelimon Emergency Clinical Hospital Bucharest (2011-2020) found that most tumour locations were stomach (49.12%) and sigmoid (3.5%) but no rectum. 12 Mesenchymal tumours of the prostate with spindle cell patterns required a comprehensive differential diagnosis. This case lacked specific clinical signs and symptoms, as well as laboratory findings.…”
Section: Discussionmentioning
confidence: 99%
“…4 A study of Ceausu et al found that the sensitivity of preoperative CT-scan was 84.61% from 39 patients. 12 In diagnosing E-GIST, the origin of tumours in the gastrointestinal tract should be removed. Few GISTs are rectum-related, and some of these cases are mistakenly identified as prostatic E-GIST.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent advances in diagnosis and treatment, the 5-year OS remains poor. Moreover, gastrointestinal stroma tumor is a rare but highly curable cancer and has a satisfactory prognosis with a 5-year OS ranging from 60%-85%[ 18 , 19 ]. Notably, multimodal complications associated with radical gastrectomy during perioperative period should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, according to previousstudies, approximately 40-70% of GISTs originate in the stomach, 20-40% in the small intestine, and less than 10% in the rectum, colon, and esophagus [10]. Those are known as extra-gastrointestinal stromal tumors (eGIST) and typically behave aggressively [11]. On the other hand, the retroomentum, uterus, and mesentery are examples of extraintestinal sites where GISTs can grow [9].…”
Section: Introductionmentioning
confidence: 99%